Students, Radicalism, and Entrepreneurship (A Case Study at IAIN Curup) - Hendra Harmi; Lukman Asha; Yuyun Yumiarty (AJIS: Academic Journal of Islamic Studies, 2020)
The objectives of this study were to find out the extent of radicalism-related understanding and symptoms amid the students of IAIN Curup and to know the policies made by the campus in countering radicalism. This study applied a descriptive analytic method adopting a phenomenological approach that deployed some techniques of collecting data such as observations, interviews, and documentation. This study revealed that the understanding of radicalism among the students of IAIN Curup was associated with religious radicalism. However, there was no any radicalism symptom found. In general, the students of IAIN Curup still had the spirits of Pancasila, Bhineka Tungga Ika, NKRI and the 1945 Constitution. The policies made by the campus in counteracting radicalism extended to strengthening the understanding of diversity, the mastery of scientific fields, and entrepreneurship. Students had an understanding of religious tolerance and accepted the presences of others. An active engagement into students’ activities made them stay focused on the objectives of lecturing and learning. Through entrepreneurship activities, students became creative and innovative so that they were not easily drawn into radical actions